2016
DOI: 10.1177/1470320316669880
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of systemic renin-angiotensin system peptides of hypertensive black and white African men established from the RAS-Fingerprint®

Abstract: Objective:The objective of this study was to make use of a quantitative and qualitative approach comparing the systemic renin-angiotensin system (RAS) of hypertensive black and white African men by using RAS equilibrium analysis.Materials and methods:This sub-study involved 23 black (n = 15) and white (n = 8) hypertensive men aged 39.5–41 years, living in the North West Province of South Africa. The RAS-Fingerprinting was determined with LC-MS/MS quantification of angiotensin peptides. Blood pressure and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…• Black populations, whether residing in Africa, the Caribbean, United States, or Europe, develop hypertension and associated organ damage at younger ages, have a higher frequency of resistant and nighttime hypertension, and a higher risk of kidney disease, 131 stroke, HF, and mortality, 132 than other ethnic groups. • This increased cardiovascular risk may be due to physiological differences including a suppressed RAAS, 133,134 altered renal sodium handling, 135 increased cardiovascular reactivity, 136 and early vascular aging (large artery stiffness…”
Section: June 2020mentioning
confidence: 99%
“…• Black populations, whether residing in Africa, the Caribbean, United States, or Europe, develop hypertension and associated organ damage at younger ages, have a higher frequency of resistant and nighttime hypertension, and a higher risk of kidney disease, 131 stroke, HF, and mortality, 132 than other ethnic groups. • This increased cardiovascular risk may be due to physiological differences including a suppressed RAAS, 133,134 altered renal sodium handling, 135 increased cardiovascular reactivity, 136 and early vascular aging (large artery stiffness…”
Section: June 2020mentioning
confidence: 99%
“…However, in non-obese normotensive German men (age 25 years), angiotensinogen associated positively with leptin [38], thus suggesting the potential role of RAS in the link between leptin and blood pressure in our study. However, black populations are known to have lower renin, angiotensin I and II levels compared to whites [39,40], possibly explaining the lack of association between DBP and leptin in black men. More research is necessary to establish a link between leptin and the RAS system in Africans.…”
Section: Leptin and Blood Pressurementioning
confidence: 98%
“… 30 Several other studies have shown that Ang-(1–7) concentrations are often very low or immeasurable in states of health and disease. 31 , 32 While we did not measure ACE2 activity, we are the first to quantify the effector molecules of the alternative RAS in these patients. Our results suggest that Ang-(1–7) might be quickly metabolized to Ang-(1–5) in patients without ACE inhibitors as most patients without RAS blockade or on ARB had detectable Ang-(1–5) levels, indicating an ongoing activity of the alternative RAS axis.…”
Section: Discussionmentioning
confidence: 99%